Abundance and phenology of Schizomida (Arachnida) from a secondary upland forest in Central Amazonia - Adis, Joachim U.; Cokendolpher, James C.; Reddell, James R.; Rodrigues, José Maria G. (Revue Suisse de Zoologie, 2001)
The 357 Schizomida (short-tailed whipscorpions) collected within 12 months from the soil (0-7 cm depth) of a secondary upland forest (60.4 ± 32.2 ind./m2/month) near Manaus are represented by the hubbardiids Surazomus mirim and S. rodriguesi (99.7% and 0.3% of the total catch, respectively). About 74% of all specimens of S. mirim inhabited the organic soil layer (0-3.5 cm depth) where monthly catches of juveniles were negatively correlated with temperatures of the soil. Females were twice as abundant as males. The lack of a distinct reproductive period and the presence of juveniles (in particular the first nymphal instar) and adults (both sexes) throughout the year indicate a plurivoltine mode of life. Few specimens were caught on the soil surface, none on tree trunks. Abundance of S. mirim is compared with that of the Palpigradi (micro whipscorpions) and Uropygi/Thelyphonida (vinegaroons) from the same study site. Schizomids obtained from the soil of four other upland forests in Central Amazonia (0-14 cm depth) accounted for ≤ 0.1% of the total arthropod fauna at these localities and were represented by three additional species.